Dermatologic Toxicities of Targeted Therapy and Immunotherapy in Head and Neck Cancers - Espinosa, Maria L.; Abad, Chelsea; Kurtzman, Yaira; Abdulla, Farah R. (Frontiers in Oncology, 2021)
Treatment of head and neck cancers requires multidisciplinary collaboration to reduce morbidity and mortality associated with the tumor burden, as well as to preserve function of organs and structures. With the use of various new targeted therapies come new adverse events including dermatologic toxicities, which may consist of xerosis, nail and hair changes, morbilliform or papulopustular rashes, to more severe eruptions such as Stevens–Johnson syndrome. We describe the dermatologic toxicities and corresponding grades of severity and associated pathophysiology resulting from seven therapeutics used to treat head and neck cancers: cetuximab, trastuzumab, pembrolizumab, nivolumab, lentatinib, larotrectinib, and entrectinib. Being familiar with these dermatologic toxicities allows clinicians to provide comprehensive counseling for patients, encourage preventative measures, and to know when it is appropriate to hold therapy or permanently stop treatment.